Et nybabylonisk gravfund fra Bahrains oldtidshovedstad - Glob, P.V. (Kuml, 1956)
A Neo-Babylonian Burial from Bahrain's Prehistoric Capital The excavations on which the Danish Archeological Bahrain-Expedition had in previous years been working - the prehistoric temples near Barbar 1) and the prehistoric capital city at Qala'a 2) - could be taken up again immediately on the opening of the third campaign 8th January 1956. In this campaign, which lasted until 20th April, the present author took part as leader, the other members being, from the previous year, T. G. Bibby, M. A., Kristian Jeppesen, mag. art., Mogens Krustrup, mag. art., and, for the first time, Harald Andersen, Keeper, and Peder Mortensen, Assistent Keeper, both from the Prehistoric Museum, Frode Visti, conservator, and Toto Koopmann of the London University Archaelogical lnstitute. For a short period the Lord Mayor of Aarhus, Svend Unmack Larsen, took part in our work, while Karl Bovin, artist, used the Expedition headquarters throughout as the centre for his entomological studies. The Ruler of Bahrain, His Highness Shaikh Sulman bin Hamad Al-Khalifah, showed as always the greatest kindness to the members of the expedition, visiting the excavations and our camp, which this year was erected in the ruins of the Portuguese fort that crowns the tell which covers Bahrain's prehistoric capital. Grants from the Government of Bahrain, from the Bahrain Petroleum Company and from the Carlsberg Foundation had ensured the economic basis of the Expedition. As always, our work in Bahrain was followed throughout with the greatest interest and helpfulness by Sir Charles Belgrave, the Adviser to the Government, and by E. A. Skinner, the Vice-president of the Bahrain Petroleum Company. Two phases of the investigations at Barbar are described separately in some detail by the excavators (cf. pp. 195 and 186). In addition sections through the occupation levels east and south of the temple buildings were cut and drawn, enabling a definite stratigraphy of the three building periods to be established. The excavation of these temples is not yet complete but will be continued in further campaigns. At Qala'a work continued on several fronts. The large-scale investigation of the stratigraphy of the "tell", consisting of the cutting and drawing of a section from the seashore towards the centre of the mound, was continued, and reached levels with a pottery content proving contemporaneity with the Barbar temples. The succession of strata representing the successive occupations of the ancient capital of Bahrain are thereby now determined from the present day back as far as the third millenium BC. To this latter period also belongs the large building which is still being excavated, as is shown by the fact that its lowest floor level and its construction level contain the same characteristic ridged pottery as is typical for Barbar 3). This ware has also now been found in the Bahrain grave-mounds, a characteristic vessel of the type being rescued by the Rev. Alun Morris of Manama when some mounds were razed in the course of road construction north of Rifa'a Al-Gharbi. Towards the end of the 1955 season, near the point in the large building at Qala's where earthenware sarcophagi were found in the first campaign, a level stretch of plaster had been discovered, measuring about 1.75 X 2 metres and surrounded on all sides by walls. At the commencement of this season it was discovered that this plaster covered a similar sarcophagus, this time untouched and with its roof-stones still in position. The sarcophagus was of lightly fired clay, covered on the outside and upper edge with a layer of bitumen a couple of millimetres thick; it was one metre long and 65 cms. wide at the top, and stood in the southern half of the space bordered by the walls (Fig. 3). It was obvious that this space had originally been used for other purposes and that the coffin had been later deposited in it and covered, first with planks, then with a layer of plaster, then with two large limestone slabs, and finally with the level plaster layer covering the whole area. lmmediately under this plaster layer, in the northwest corner of the room, lay three small vessels of light yellowish clay, wheel-made, (Fig. 2) presumably placed there as funerary offerings. Between the stones that adjoined the sarcophagus to the west were found three small copper or bronze arrowheads, of triangular section and with a short shaft-socket (Fig. 5). By the southwest corner of the coffin stood an iron spearhead, stuck into the floor with the point downwards. The actual sarcophagus, 65-75 cms. deep - interior dimension -, was almost completely empty of soil, the bottom being only partly covered with a grayish layer (Fig. 3). It was oriented east-west, with the rightangled end, where the head of the occupant rested, towards the west (Fig. 4). The bottom of the coffin was covered with skeletal parts and funerary furnishings. The dead body - to judge by the size of the bones and the type of furnishings probably a man - rested on its left side in a sharply contracted position, with its knees pressed right up against the breast and with its hands in front of its face, which was turned to the north (Fig. 4). The bones still showed in the main the position in which the dead man had originally been placed; only at the western end of the coffin were they in some disarray, perhaps disturbed by a snake as the cast skin of a snake was found between the roof-stones of the coffin. The furnishings of the grave were very rich. In the centre of the sarcophagus, near the vertebral column, lay an agate seal, pierced at the top and with the pierced hole towards the neck of the dead man, which would suggest that he had carried it on his breast on a cord hanging from his neck (Fig. 4 no. 13). This seal is 31 mms. tall, conical in form, rounded at the top and slightly convex at the base where the design is engraved (Fig. 1). The sides are facetted, the facet following the edge at the base (Fig. 5). Stamp seals of this type came into use again in Mesopotamia in late Neo-Assyrian and Neo-Babylonian times, the earliest group being dateable to the 8th century BC4). This seal shows a male worshipper with a full beard and raised hand, turned towards the tree of life. Between them there is the figure of a fish, and above them the winged solar disk (Fig. 1). ldentically the same group, though represented in greater detail, is known from cylinder seals from the late 8th or 7th centuries 5), to which date therefore the seal and the remaining contents of the grave must be dated. The great resemblance between this grave and those found during the first campaign in the same building, for which an earlier date was previously proposed 6), makes it now reasonable to attribute these also to the 8-7th centuries BC. At the foot-end of the coffin lay a glazed vase, wheel-made and 29.5 cms. high (Fig. 4 no. 1 and Fig. 6). The glaze, which covered the entire vessel but is somewhat corroded, is of a light greenish colour around the neck and lip. In front of the dead body lay four different objects of copper or bronze: a flask, 19.5 cms. high, with a swivelling handle (Fig. 4 no. 2 and Fig. 7 no. 1); a circular bowl, 20.5 cms. in diameter and 4 cms. deep, with a slightly outturned rim (Fig. 4 no. 5 and Fig. 7 no. 2); a strainer, 10.5 cms. in diameter, with an 11.5 cm. long handle, bent round at the end and ending in a duck's head (Fig. 4 no. 3 and Fig. 8 no. 1); and a pouring vessel, 7 cms. high, with a 25 cm. long handle, bent back at the free end and broadening out into a tongue where it meets the lip (Fig. 4 no. 4 and Fig. 8 no. 2). In addition there lay in the centre of the coffin and in front of the dead man a tanged iron dagger, 30 cms. long (Fig. 4 no. 15 and Fig. 5); together with 6 copper rings (Fig. 4 nos. 6-7 and 9-12), while a similar ring lay by the bones of the feet (Fig. 4 no. 14 and Fig. 5). As in the former campaigns, reconnaissance in the desert areas of Bahrain was continued on the weekly holidays, when the major excavation work ceased, and in the course of this reconnaissance a further series of discoveries was made of flint artifacts of palaeolithic and neolithic derivation, but of the same types as those earlier discovered 7). On one of these days an opportunity was provided by the particular generosity of His Highness Shaikh Sulman of visiting the large island of Umm Nasan, which lies off the west coast of Bahrain and is protected as a game reserve. Here a number of cubical rock tombs, about 3---4 cubic metres in size, were found cut out of the southwestern side of the southerly of the two rocky hills of the island. They were all, however, completely empty. As in previous years our work aroused very great interest among all circles in Bahrain. A large number of visitors continously honoured our excavations and our camp. We received help and hospitality from many quarters. For a short time we were all living at the guest house of Petroleum Concessions Limited, where we were very kindly received by M. E. Welford. The director of the Public Works Department, M. Lees, gave us ready help when heavy equipment was required. The leading figures of the Bahrain Petroleum Company showed unfailing interest, and the General Manager, J. R. Keith, gave us his personal support in many matters. The expedition owes a particular debt of thanks to the Vice-President of the Company, E. A. Skinner, who from the first showed the greatest friendship and understanding to us and to our work, and who, together with Mrs. Skinner, frequently offered us the hospitality of his beautiful home. The news of his recent death caused a deep sense of loss to all members of the Danish Archeological Bahrain-Expedition. P. V. Glob